A study of toxic elements and radionuclides in semi-smoked sausages made with lentils, thyme, and juniper - Paska, Maria; Simonova, Iryna; Galuch, Bogdan; Basarab, Iryna; Masliichuk, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
The study determines toxic elements by methods of atomic absorption spectrometry with atomisation in a flame in terms of the colorimetric atomic absorption method. The values of specific activity and volumetric activity of γ-emitting radionuclides are found in sausages using the means of computer technology. The purpose of the research is to determine the safety of semi-smoked sausages made with the use of beef, poultry, lentils, thyme, and juniper as to the content of toxic elements and radionuclides by using techniques developed by Lviv Oblast State Laboratory of the State Consumer Protection Service in Lviv Oblast. A detailed description of the process of conducting research on the sausages is given in the article. Semi-smoked sausages of modified recipes, namely using beef, poultry, lentils, thyme, and juniper, were investigated according to the methodology developed by Lviv Oblast State Laboratory of the State Consumer Protection Service in Lviv Oblast, using the atomic absorption spectrometry method applying Varian AA240FS Atomic Absorption Spectrophotometer (Agilent Technologies, USA) and Shimadzu AAS-6300 Atomic Absorption Spectrophotometer (Shimadzu, Japan). The use of the developed techniques and this equipment made it possible to determine the contents of lead, cadmium, mercury, arsenic, copper, zinc, and radionuclides and to confirm conformity of the sausages according to these parameters to the requirements of DSTU 4435:2005. Semi-smoked sausages. The research results allowed registering the technical specifications and technological instructions for the semi-smoked sausages Osoblyva Simeyna, Osoblyva Simeyna Spiced, Osoblyva Sambirska, Osoblyva Sambirska Spiced, Osoblyva Stryiska, and Osoblyva Stryiska Spiced.